The influence of individual and contextual variables on the rating behaviors of self, peer, subordinate, and supervisor raters - Kerst, Melinda E., author; Cleveland, Jeanette N., advisor; Thornton, George C., III, committee member; Bell, P. A., committee member; Slater, Michael, committee member (Colorado State University. Libraries, 2000)
Data collected from undergraduate Psychology students who engaged in a performance evaluation task were used to examine the relationships among rater role (self-rater, peer-rater, subordinate-rater, supervisor-rater), rating purpose (administrative, developmental) and rating behavior (rating leniency, discrimination among performance dimensions, discrimination among ratees). Significant main effects were found for rater role on rating leniency and on discrimination among performance dimensions. A significant main effect was also found for rating purpose on rating leniency. In addition, results for an interaction between role and purpose on behavior were significant for rating leniency and for discrimination among performance dimensions. Individual (self-esteem, locus of control) and contextual (affect, self-efficacy, politics, organizational commitment) variables were examined as covariates of rating behaviors associated with the different rater roles. Although substantial variance in rating behavior was accounted for by these covariates (e.g., self-esteem, locus of control, affect, efficacy, politics, organizational commitment), results were not in the direction predicted. Individual characteristics and contextual variables were found to account for significant variance in the rating behavior of self-rater. Implications of findings in terms of contributions to the literature and application to organizations are discussed.
Keywords: studies; college students; correlation analysis; perceptions; self image; access to information; ratings and rankings; self esteem; bias